Treinamento e desenvolvimento de pessoas e a nova gestão pública : o caso do Projeto Formação de Tecnólogos em Gestão Pública do Governo do Rio Grande do Norte - Oliveira Júnior, Paulo César Medeiros de (2011)
This thesis aims to identify how civil servants perceive changes made inthe carrying out of their work after their taking part in the Course forTechnicians in Public Management of the Government of Rio Grande do NorteState. As for the methodological procedures, an exploratory-descriptivequantitative research has been carried out through structured questionnaires appliedto 118 civil servants from the first groups of the Course for Technicians, thusshowing a margin of error of 4.18% to 95% of confidence, according to theprocedures of finite sampling. The table processing and analysis rested uponthe Statistical Package for the Social Sciences SPSS and was carried outthrough univariate, bivariate and multivariate techniques with emphasis on thetechnique called Factor Analysis. It was possible to identify that the level ofsatisfaction of the students was high and there was a clear perception by themthat the course assisted to changes in their work. Through Factor Analysis itwas verified that the factors that may be related to changes in the work of thecivil servants are "Contribution to Society", "Efficiency andEfficacy in the Work Environment", "Applicability of Contents"and "Capacitating for Leadership". The conclusion of the studyindicates that the factors obtained are directly related to the basis of thenew public management by means of guidance toward efficiency and efficacy in aperspective of leadership, the contents of the course being thus made into newattitudes toward work which end up yielding better results for society